Improvement of Crop Plants for Industrial End Uses - RANALLI, P.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Advanced biotechnologies enable breeders to produce a whole generation of new crops for specialist needs ("designer crops"), including raw materials for the energy, chemical and pharmaceutical industries. This book provides concerns useful to promote an increase of the productivity of crops by using functional genomics (to understand the regulation of plant metabolism at molecular, cellular and whole plants), and the improvement of photosynthetic efficiency (to design new plants with enhanced raw materials percent and recovery). Fundamental thematics have been addressed: metabolic engineering, plant breeding tools, renewable biomass for energy generation, fibres and composites, biopharmaceuticals. The gained know how is relevant to identify bottlenecks in the major production chains and to propose actions for moving these issues forward: in particular to; i) produce new compounds by expressing foreign heterologous genes; ii) modify pathways to influence quality and/or yield of existing indigenous molecules; iii) bioprocess plant or organic waste stream into value-added products. The chapters of this book have been written by experts from all around the world.
The use of functional genomics to understand components of plant metabolism and the regulation occurring at molecular, cellular and whole plant levels -- Improving photosynthesis and yield potential -- Marker assisted selection and genomics of industrial plants -- Improved agronomy and management of crop plants for industrial end uses -- Lignin manipulation for fibre improvement -- Improvement of fibre and composites for new markets -- In planta novel starch synthesis -- Bioethanol: role and production technologies -- Complex lipid biosynthesis and its manipulation in plants -- Biodiesel production -- Bioelectricity and cogeneration -- Genetic improvement of crops for energy generation: comparison of different provision chains with respect to biomass and biofuel production -- Anaerobic digestion: a multi-faceted process for energy, environmental management and rural development -- Molecular farming for antigen (vaccine) production in plants -- Molecular farming of antibodies in plants -- Molecular tailoring and boosting of bioactive secondary metabolites in medicinal plants -- Potential market for bio-based products in the context of European greenhouse gas reduction strategies.
Keywords: LIFE SCIENCES; BIOCHEMISTRY; PROTEOMICS; DEVELOPMENTAL BIOLOGY; BOTANY; PLANT BREEDING; LIFE SCIENCES; PLANT SCIENCES; PLANT BIOCHEMISTRY; PROTEOMICS; PLANT GENETICS & GENOMICS; DEVELOPMENTAL BIOLOGY